OPTIMIZING THE QUALITY OF NURSING CARE DOCUMENTATION THROUGH NURSING SUPERVISION TRAINING IN THE INPATIENT ROOM OF RSIA BUNDA DENPASAR - Prihandhani, IGAA Sherlyna; Bulan Trisna, Made Oktaviani; Widiastuti, Putu (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Hospitals are health service organizations providing integrated care by professional caregivers, including doctors, nurses, nutritionists, and pharmacists. Nursing care documentation is essential for patients, nurses, and the entire health team involved in service delivery. Complete documentation supports continuity of patient care, facilitates coordination among professionals, and contributes positively to patient safety. Therefore, the completeness of nursing documentation plays an important role in improving the overall quality of health services provided by hospitals in daily clinical practice settings. Subjective: This study aims to determine the optimization of the quality of nursing care documentation through nursing supervision training at RSIA Bunda Denpasar. Methods: This study uses a pre-experiment method with a one group pre-test post test design. This study included a population of 38 nurses on duty in inpatient and the sample in this study was taken with a total sampling technique of 38 people. This study uses the wilcoxon signed rank test. Results: The results of the Wilcoxon signed rank test obtained a significance value of < 0.005 for each variable so that supervision training was obtained to be able to optimize the quality of nursing care documentation through nursing supervision training in the Inpatient Room of RSIA Bunda Denpasar. Conclusion: Based on the research conducted, it can be concluded that the provision of proctor and reflective model supervision training is able to optimize the quality of nursing care documentation through nursing supervision training in the Inpatient Room of RSIA Bunda Denpasar.